Deliberate self harm in adolescents: self report survey in schools in England. - Hawton, K; Rodham, K; Evans, E; Weatherall, R (2002)
OBJECTIVE: To determine the prevalence of deliberate self harm in adolescents and the factors associated with it. DESIGN: Cross sectional survey using anonymous self report questionnaire. SETTING: 41 schools in England. PARTICIPANTS: 6020 pupils aged 15 and 16 years. MAIN OUTCOME MEASURE: Deliberate self harm. RESULTS: 398 (6.9%) participants reported an act of deliberate self harm in the previous year that met study criteria. Only 12.6% of episodes had resulted in presentation to hospital. Deliberate self harm was more common in females than it was in males (11.2% v 3.2%; odds ratio 3.9, 95% confidence interval 3.1 to 4.9). In females the factors included in a multivariate logistic regression for deliberate self harm were recent self harm by friends, self harm by family members, drug misuse, depression, anxiety, impulsivity, and low self esteem. In males the factors were suicidal behaviour in friends and family members, drug use, and low self esteem. CONCLUSIONS: Deliberate self harm is common in adolescents, especially females. School based mental health initiatives are needed. These could include approaches aimed at educating school pupils about mental health problems and screening for those at risk.